تحليل نقدية للأخطاء النحوية في الرسائل الجامعية لطلاب تعليم اللغة العربية: Grammatical Error Analysis in Undergraduate Theses of Arabic Language Education Students - Ayu, Ayu Lestari; Muhaemin (Institut Agama Islam Negeri (IAIN) Palopo, 2025)
This study aims to analyze grammatical errors found in undergraduate theses written by students of the Arabic Language Education Department at the State Islamic University of Palopo (2020–2023). The study focuses on fifteen purposively selected theses that contained a high frequency of linguistic errors. Particular attention was given to the abstract and introduction sections, as they are indicative of students’ foundational language proficiency and academic writing skills. A descriptive-analytical method was employed, utilizing document analysis and semi-structured interviews with both students and academic supervisors. The findings reveal five major categories of grammatical errors: construct phrase, adjective–noun agreement, number agreement, sentence structure, and prepositional usage. Among these, errors were the most frequent, followed by mismatches in adjective–noun agreement. Interview results suggest that these errors stem from multiple factors, including limited theoretical understanding of Arabic grammar, insufficient writing practice, overreliance on machine translation, first-language interference, and inadequate linguistic supervision during the thesis writing process. The study recommends strengthening Arabic writing instruction through structured practice, ongoing feedback, the use of grammar-checking tools, and increased involvement of supervisors in language-focused mentoring. This study offers a comprehensive overview of the challenges faced by Arabic language learners in academic writing and proposes pedagogical strategies to improve grammatical accuracy and elevate the quality of students' written academic output.تهدف هذه الدراسة إلى تحليل الأخطاء النحوية في الرسائل الجامعية التي كتبها طلاب شعبة تعليم اللغة العربية في الجامعة الإسلامية الحكومية بفالوفو خلال الفترة ما بين 2020 إلى 2023، وذلك من خلال دراسة عيّنة مكونة من خمس عشرة رسالة تم اختيارها عمدًا لاحتوائها على عدد كبير من الأخطاء اللغوية. ركزت الدراسة على تحليل الأخطاء في قسمَي الملخص والمقدمة، لما لهذين الجزأين من أهمية في الكشف عن المهارات اللغوية الأساسية لدى الطلبة. اعتمدت الدراسة المنهج الوصفي التحليلي، واستخدمت أدوات جمع البيانات المتمثلة في تحليل الوثائق والمقابلات النصف الموجهة مع الطلبة والمشرفين الأكاديميين. وقد كشفت النتائج عن وجود خمسة أنماط رئيسية من الأخطاء النحوية، وهي: أخطاء الإضافة، وأخطاء الصفة والموصوف، وأخطاء العدد والمعدود، وأخطاء بنية الجملة، وأخطاء استخدام حروف الجر. وبيّنت النتائج أن أكثر هذه الأخطاء شيوعًا تتعلق ببنية الإضافة، تليها الأخطاء في المطابقة بين الصفة والموصوف. أظهرت المقابلات أن هذه الأخطاء تعود إلى عدة عوامل، من بينها ضعف الفهم النظري لقواعد النحو، وقلة الممارسة الكتابية، والاعتماد على الترجمة الآلية، إضافة إلى تأثير اللغة الأم، وغياب الإشراف اللغوي المتخصص. وخلصت الدراسة إلى ضرورة تعزيز البرامج التعليمية بتمارين كتابية منتظمة، وتقديم تغذية راجعة مستمرة، وتوظيف التقنيات الحديثة في الكشف عن الأخطاء، إلى جانب تفعيل دور المشرفين الأكاديميين في المتابعة اللغوية. تسهم هذه الدراسة في تقديم تصور شامل حول واقع الكتابة الأكاديمية لدى طلبة تعليم اللغة العربية، وتقترح مداخل عملية لتحسين جودة الكتابة، والارتقاء بمستوى الكفاءة اللغوية في السياقات الجامعية.